Effects of Heat Treatment and Deformation on Microstructure and Properties of Cu–Ni–Si Alloy/AA8030 Alloy Composite Wires - Shuke Tian; Fan Zhao; Xinhua Liu (Metals)
The influence of heat treatment and deformation on the microstructure and properties of a Cu–Ni–Si alloy/AA8030 alloy composite wire was studied. After aging at 450 °C for 60 min, the composite wire exhibited relatively high comprehensive properties, with ultimate tensile strength, elongation, and electrical conductivity values of 253 MPa, 11.1%, and 55.3% IACS, respectively. Microstructural analysis revealed that precipitation and dislocation strengthening played important roles in the aged Cu–Ni–Si alloy cladding, whereas grain boundary and dislocation strengthening contributed to the strength of the AA8030 alloy. Then, the wire underwent five passes of drawing with a total deformation of 75%. Significant work hardening changed the ultimate tensile strength, elongation, and electrical conductivity of the composite wire to 422 MPa, 3.3%, and 53.6% IACS, respectively. CuAl2, CuAl and Cu9Al4 layers were formed at the composite interface during aging. The CuAl2 and Cu9Al4 layers grew toward the Al alloy and Cu alloy, respectively, whereas the CuAl layer grew toward both the Al alloy and the Cu alloy.